Stop Covid-19 Crisis Morphing into A Food Crisis: Support To Africa’s Rice Sector - CGIAR Research Program on Rice (2020)
The paper aims to inform decision-makers and other stakeholders in the rice sector in Sub-Saharan Africa about the potential impact of the COVID19 crisis to trigger actions.